(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Mud crab is fishery commodity that has high economic value and rich of nutritional aspect such as essential amino acids, vitamins, minerals, and fatty acids. In addition, high concentrations of heavy metals in the natural habitat of crabs can accumulate in these organisms which can endanger health if consumed. However, there is little information regarding the nutritional and heavy metal content of meat and byproducts in mud crab. The objective of the study are to compare the beneficial component of the meat and byproduct of Scylla paramamosain and to investigate food safety from heavy metal contamination. Proximate, vitamin A, D, and E content were analyzed using HPLC, vitamin B1, B2, C, and amino acid profile was determined by using UPLC, vitamin B12 was determined by LC-MS, mineral and heavy metal were determined by standard method of AOAC. In addition, the determination of fatty acid was analyzed by gas chromatography. Result showed that protein per gram as the majority content of each form (10.24% in crab meat and 12.47% in byproduct). Vitamin B2, B12, and E were detected in sample. On contrary, heavy metals examined in this study were not detected. L-Glutamic acid was the most abundant of amino acids composition (11037.79 mg/kg of crab meat and 15993.22 mg/kg of byproduct), while omega-3 fatty acids, omega-6 fatty acids, and omega-9 fatty acids are also contained in this species. The result showed Scylla paramamosain as source of beneficial food and safe to consume.